Woman's Role In Secretariat (2010) Directed By Randall Wallace: A Feminist Approach - Febrianto, Devi (2012)
The object of this research is the movie entitled Secretariat by Randal Wallace. The major problem of this study is how the role of woman reflected in movie Secretariat movie (2010) Directed by Randal Wallace. The research sets two objectives: the first is to analyze the movie based on the structural elements of the movie, and the second is to analyze the movie based on the Feminist Perspective. This study belongs to qualitative study. In this method, the researcher uses two data sources, namely primary and secondary data source. The primary data source and the object of the study is the movie Secretariat itself, meanwhile secondary data are reviews of the film which are collected from various sources and other data which deal with the research, such as, from the journal, website and other references that has connection with the research. The outcome of the study is as follows: first, based on the structural analysis of each elements, it shows that the character and characterization, plot, point of view, setting of place and time, mise-en- scene, cinematography, editing, and the other technical elements have the unity and successfully relate to one another then finally are formulated into good quality of a movie. Second, based on the Feminist analysis, the writer concludes that the role of woman is no less than men, even woman can be better than men. Penny can run dual roles well in the issue of women's position, rights, role, and participation. The last, based on social background, there is close relation between the production of this movie and the social reality underlying it, such as social status and women condition. This movie tells the struggle of woman to show her roles in the society.